METHOD OF DEVELOPING STUDENTS' SENSE OF ENGAGEMENT IN HISTORY THROUGH COGNITIVE-REFLECTION - Azimov Mukhammadi Azim oglu (Bright Mind Publishing, 2026)
The article describes the essence, purpose, significance of the development of a sense of involvement in history in students of education using the cognitive-reflexive method and a set of pedagogical views related to the supreme law. , its production processes, integration processes into the educational process and educational processes, educational processes. In addition, this research work provides proposals for cognitively ensuring a sense of involvement in history in students.
Keywords: Involvement, cognitive-reflexivity, pedagogical technology, experimental control, Bloom's taxonomy, reflexive questions, indicator and level.